Time to Think Antifungal Resistance - Thomas McCormick; Mahmoud Ghannoum (Case Western Reserve University, 2024)
Increased antifungal resistance is exacerbating the burden of invasive fungal infections, as well as potentially contributing to the increase in resistant dermatomycoses. In this commentary, we focus on antifungal drug resistance, in contrast to antibacterial resistance. We provide a brief historical perspective on the emergence of antifungal resistance and propose measures for combating this growing health concern. The increase in the incidence of invasive and cutaneous fungal infections parallels advancements in medical interventions, such as immunosuppressive drugs, to manage cancer and reduce organ rejection following transplant. A disturbing relatively new trend in antifungal resistance is the observation of several fungal species that now exhibit multidrug resistance (eg, Candida auris, Trichophyton indotineae). Increasing awareness of these multidrug-resistant species is paramount. Therefore, increased education regarding potential fungus-associated infections is needed to address awareness in the general healthcare setting, which may result in a more realistic picture of the prevalence of antifungal-resistant infections. In addition to education, increased use of diagnostic tests (eg, micro and macro conventional assays or molecular testing) should be routine for healthcare providers facing an unknown fungal infection. Two critical barriers that affect the low rates for Antifungal Susceptibility Testing (AST) are low (or a lack of) sufficient insurance reimbursement rates and the low number of qualified laboratories with the capacity to perform AST. The ultimate aim is to improve the quality of patient care through fungal identification, diagnosis, and, where appropriate, susceptibility testing. Here we propose an all-encompassing call to action to address this emerging challenge.